Polynesian Kingship and the Potlatch - Morgan, R. Christopher (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1989)
The form of exchange seen in the potlatch is gift reciprocity which validates position in systems where ranks realign over the generations. Improved understanding of movement in hierarchy within a relatively centralized system from Polynesia stimulates fresh comparison between the Northwest Coast and Oceania. The complex stratified policy of Tonga entails rivalry and competition for title between members of the ranking elite. Competitive exchange is part of wider relations between titleholders and their supporting groups though it does not itself determine rank. Calculations to lift rank are made through marriages and warfare which bring control over the accumulation, distribution and acceptance of gifts.